Features of the correlation of information and legal culture - Онопрієнко, Станіслав Григорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article based on an analysis of categories of «information culture», «legal culture», «sense of justice» and «information awareness» carried the distinction of the latter and defined the characteristics of their mutual influence. Cognition of any phenomenon or process requires a conditional division of the subject of research into constituent elements, the totality of which, as well as the relationships between them, arise, and allows us to use the system approach, simulate the consequences of changes in one component on the functioning of the entire system. This is especially important for those phenomena, the study of which is in the initial stage of its development. The category of "information culture" has recently become a part of scientific usage; discussions about its concept and content are still under way. This determines the relevance of the article, the purpose of writing was to offer the author's version of the classification of elements of the information culture.The author based on the analysis of works in the field of the theory of law concluded that in the legal science there are several categories: "legal culture", "information culture", "legal consciousness" and "information consciousness." The author considers the relationship between them. It was established that common to these approaches is the understanding of information culture as a component of the general culture in the society, as well as recognition of the links between the level of determination of information culture and the development of a certain sphere of professional activity of the person.Without the presence of characteristic information culture elements, in particular, the ability to receive from various sources, analyze certain information, draw conclusions from them, structure the information received, and form a sense of justice is impossible. Therefore, the information culture, acting simultaneously as one of the types of a common culture, along with the legal one, is not autonomous, isolated in relation to the sense of justice, it is a prerequisite for the development of the latter, and, at the same time, the means of its formation. At the same time, it can not be asserted that a high level of information culture determines a high level of legal awareness. Unfortunately, possession of the achievements of the information culture of mankind can be combined with a high level of legal nihilism, that is, the primary values in this case are the person's value orientations. At the same time, it is impossible to achieve a high level of legal culture without a high level of information culture, as it seems to us, since the individual must rework a large amount of legal information, constantly monitor changes in legal reality, for which he must have the relevant knowledge, skills and skills that characterize him Information competence.